Migrations et frontière : le cas de Saint-Martin - Marie Redon (Études Caribéennes)
The small Caribbean island of St. Martin (90 km ²) saw its population nearly tripled in the last two decades, from 25 000 to about 70 000 islanders. The intra-Caribbean migrations are the main cause of significant population growth of the mid-French, mid-Dutch island where standard of living is comparable to that of Western Europe but located in a geographical area less privileged. The article tends to question the causal link between the massive influx of immigrants populations and the partition of the island, the latter factor appearing crucial for understanding the phenomenon of migration to Saint-Martin. The island would be made more attractive by the existence of this border which, on the one hand, promotes a particular economic dynamism and, on the other hand, gives the control of migration flows more difficult because of the legislative differential between its two parties.